The productivity increasing of peatlands on community land by multi-cropping model in Riau Indonesia. (December 2019) - Ariyanto, D P; Sumarno,; Supriyono,; Yunus, A; Pudjiasmanto, B; Rahayu,; Widijanto, H; Suntoro,
Abstract: Development and protection of peatlands become important things to reduce land damage, such as peatland fires, and can increase economic value for farmers. This research aims to evaluate the development of peatlands which friendly. The conduct was August 2017 to June 2019 in Merbau, Bunut Regency-Province of Riau, Indonesia. The area has 3 peatlands; those are shallow, medium, deep, and enrichment peat. The results showed that multi-cropping could be cultivated to some plants, those are Liberika coffee, rubber, and Areca nut for annual plants. Besides that, a pineapple could be cultivated among annual plants. Monkeys and wild boars are seriously affecting independence to cultivation. Community and farmers approach with public figure become the key to land management without peatland fires.